A cybersecurity platform for simulating transient responses of emulated programmable logic controllers in instrumentation and control systems for a pwr plant - El-Genk, Mohamed; Schriener, Timothy (Journal of cyber security, 2022)
This research used the developed LOBO Nuclear CyberSecurity (LOBO NCS) platform at the University of New Mexico to investigate potential cyber vulnerabilities of digital Instrumentation and Control (I&C) systems for components in a representative Pressurized Water Reactor (PWR) plant during simulated operation transients. This platform links physics-based MATLAB Simulink models to emulated or physical Programmable Logic Controllers (PLCs) in I&C systems. An efficient data transfer interface and broker are developed to manage and coordinate communication between the emulated PLCs and the Simulink models. Presented transient results are for the steam generator and the feedwater PLCs following an increase in steam load demand. Related results are for the pressurizer and the pressure and water-level PLCs during simulated surge-in and surge-out transients. These results are for nominal transient operations and when the emulated PLCs are subject to simulated false data injection attacks (FDIAs). Obtained results of the pressurizer and the pressure PLC using the LOBO-NCS are in excellent agreement with those using the DOE SCEPTRE framework at Sandia National Laboratories.